Analisis Strategi Pemasaran Peternakan Ayam CV Intan Jaya Abadi Sukabumi - Rizwan Nazaruddin; - Suryahadi; Ma'mun Sarma (Institut Pertanian Bogor, 2011)
The purpose of this study is to know the general strategy used CV. Intan Jaya Abadi (CV IJA) conditions in the industrial poultry farm in Sukabumi. In particular, this study aims to identify and analyze the marketing strategies of poultry farm on the CV IJA that includes aspects of supply and demand, market share, value added, financial performance, technical marketing and marketing costs and preparing the appropriate marketing strategy for managing CV IJA develop animal husbandry and poultry. Method used in this research is descriptive method, that is done to the data problems that exist and the form of research is a case study. Primary data obtained from the questionnaires and interviews with experts (business owners, marketing manager and production manager) and secondary data obtained from financial reports and product marketing company that processed data using the appropriate analysis tool, that is descriptive analysis, analysis internal and external (IE), IE matrix and Strengths, Weaknesses, Opportunitis and Threats (SWOT) matrix. Based on the identification and analysis of CV IJA success factors have remained so stable and growing among; supply and demand still high, the scope of local market still Java (90%) and West Java (10%) but can increase sales turnover, value added form of the plan companies to build the future with chicken slaughter house (RPA), the financial condition of both structures (liquid, solvable and profitable), the company has been making efficiency, the company obtained from the daily old chiken (DOC) it self, the company continues to invest to expand production capacity. Based on the analysis of marketing strategies that have been done using IE matrix, the position of marketing poultry products and eggs in the CV IJA Sukabumi is located on the quadrant II (grow and build), has the strength and the opportunities greater than the weaknesses and threat, marketing strategy and CV IJA still relevant to the environmental changes at this time. Applied strategy in the future a strategy of intensive growth or aggressive (Growth Oriented Strategy) with the strength to take advantage of the opportunities through the maintenance of product quality, production capacity, the development of scale and increase the availability of raw materials. Based on the SWOT analysis, they are then some alternative strategies provided as follows: (1) maintain and expand existing markets, (2) maintain a commitment to the management of quality products and continue to try the program to all employees, (3) doing the campaign effectively and efficient, (4) Improve the performance of marketing in analyzing the market demand, (5) Maintain and keep the quality product produced to increase customer loyalty, (6) increase collaboration with suppliers, (7) maintain the selling price in the market and (8) to improve distribution channels.